Unfavorable Prognostic Effects of the Stem Cell Pluripotency Factor Sox2 in Feline Invasive Mammary Carcinomas - Truchot, Yohan; Dagher, Elie; Abadie, Jérôme; Nguyen, Frédérique (Frontiers in Veterinary Science, 2021)
Background: Sex-determining Region Y (SRY)-box transcription factor-2 (Sox2) belongs to the “Yamanaka’s factors”, necessary and sufficient to convert somatic cells into pluripotent stem cells. In breast cancers, Sox2 expression has been associated with poor prognosis, and resistance to therapy. The aims of this study were to determine the frequency of Sox2 positivity in feline invasive mammary carcinomas (FMCs), its relationships with other clinical-pathologic variables, and with patient outcomes. Materials and Methods: This study relies on a previously described retrospective cohort of 180 FMCs, diagnosed in female cats treated by mastectomy alone, with 2-year follow-up. Sox2 (clone SP76), Estrogen Receptor alpha (ER), Progesterone Receptor (PR), Ki-67, Human Epidermal growth factor Receptor 2 (HER2), Androgen Receptor (AR), Bcl-2, Forkhead box protein A1 (FOXA1), basal markers and FoxP3-positive regulatory T cells (Tregs) were detected by automated immunohistochemistry. Sox2 expression was quantitated as an index (percentage of neoplastic cells demonstrating a positive nuclear signal). The FMCs were considered Sox2-positive at threshold >42%. Results: Sox2 was not expressed in the normal mammary gland or in mammary hyperplasia without atypia, but was occasionally detected in atypical hyperplasia. In FMCs, the mean Sox2 index was 38 ± 30%, and 79/180 FMCs (44%) were Sox2-positive. Sox2 expression was associated with older age at diagnosis, lymphovascular invasion, high Ki-67 proliferation indexes, low PR and FOXA1 expression, and increased numbers of tumor-associated Tregs, but was not significantly associated with the clinical stage, histological types, and histological grade. By multivariate survival analysis, Sox2 was associated with poor cancer-specific survival (Hazard Ratio = 1.48, 95% confidence interval 1.04–2.11, p = 0.0292), independently of the pathologic tumor size, pathologic nodal stage, distant metastasis, and AR expression. A rare subgroup of FMCs characterized by an AR+Sox2– phenotype (19/180 cases, 11%) was associated with very favorable outcomes. Conclusion: Sox2 expression was associated with poor cancer-specific survival of female cats with invasive mammary carcinomas, as previously reported in human breast cancer, but was more commonly expressed in cats than reported in breast cancers. Sox2 showed complementarity with AR in FMC prognostication.